Smaldone : the untold story of an American crime family - Kreck, Dick (Golden, Colo. : Fulcrum, 2009)
Started by Italian brothers from North Denver, the high-profile Smaldone crime syndicate began in the bootlegging days of the 1920s and flourished well into the late twentieth century. Connected to such notorious crime figures as Al Capone and Carlos Marcello, as well as to presidents and other politicians, charismatic Clyde Smaldone was the crime family's leader from the Prohibition era to the rise of gambling to the family's waning days. Uncovering the good and the bad, best-selling author Dick Kreck captures the complexity of Clyde, brother Checkers, and their crew, who perpetuated a shadowy underworld but exhibited great generosity and commitment to their community, offering food, money, and college funds to struggling families. Through candid interviews and firsthand accounts, Kreck reveals the true sense of what it meant to be a Smaldone, and the mix of love and dysfunction that is part of every American family.
Includes bibliographical references and index.
Keywords: Mafia -- United States -- Case studies; Gangsters -- United States -- Biography; Criminals -- United States -- Biography; Organized crime -- United States -- Case studies